Pengembangan Sistem Informasi Laporan Keuangan Digital Berbasis Web untuk Efisiensi Manajemen Keuangan - Dwi Puspita Anggraeni (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2023)
The effectiveness and efficiency of financial management is the key to success for trading companies such as PT Sinergi Niaga Jaya. However, manual recording methods carried out by administrative staff often cause difficulties in searching for transaction data and produce financial reports that are not comprehensive, slow down the report verification process and increase the risk of errors. This research proposes the development of a web-based digital financial reporting system to automate transaction recording and financial report generation. The developed system is designed to provide easy access for administrative staff, managers, and company owners, thus enabling more structured and efficient financial management. This research uses a quantitative approach, through observation, interviews, and literature study for needs analysis, as well as Data Flow Diagram (DFD) for data flow modeling. Testing was conducted using the Blackbox testing method to test system functionality. As a result, the system is able to generate general journal, ledger, balance sheet, profit and loss, and capital change reports automatically. This web-based financial reporting system is expected to improve the efficiency of financial management by reducing the time and risk of manual recording errors.